2016
DOI: 10.14814/phy2.12688
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory control and cytokine profile in response to heat stress, hypoxia, and lipopolysaccharide (LPS) exposure during early neonatal period

Abstract: Sudden infant death syndrome (SIDS) is one of the most common causes of postneonatal infant mortality in the developed world. An insufficient cardiorespiratory response to multiple environmental stressors (such as prone sleeping positioning, overwrapping, and infection), during a critical period of development in a vulnerable infant, may result in SIDS. However, the effect of multiple risk factors on cardiorespiratory responses has rarely been tested experimentally. Therefore, this study aimed to quantify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 78 publications
3
10
0
2
Order By: Relevance
“…Also, we did not observe an increase in leptin concentrations which has been postulated as one of the pyrogenic cytokines (Koenig et al 2014). Though we have consistently observed increased levels of TNF-α, simultaneous IL-10 concentrations also increased following LPS challenge in our current and other studies (McDonald et al 2016a;McDonald et al 2016b).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Also, we did not observe an increase in leptin concentrations which has been postulated as one of the pyrogenic cytokines (Koenig et al 2014). Though we have consistently observed increased levels of TNF-α, simultaneous IL-10 concentrations also increased following LPS challenge in our current and other studies (McDonald et al 2016a;McDonald et al 2016b).…”
Section: Discussionsupporting
confidence: 81%
“…Although a number of well-designed studies have investigated the role and mechanisms of fever and cytokine responses in the context of LPS administration in adult rodents including rats (Koenig et al 2014;Long et al 1990;Luheshi and Rothwell 1996;Machado et al 2007;Roth and De Souza 2001;Rummel et al 2011a), to our knowledge, limited data are available during early life (Fraifeld and Kaplanski 1998 inflammatory cytokines in neonatal rats and whether it is possible to delineate the effects of infection per se versus increased body temperature caused by fever. Recent studies from our laboratory have investigated inflammatory responses to LPS administration in young rat pups, however, the animals were also exposed to hypoxia and restraint stress (McDonald et al 2016a;McDonald et al 2016b); both factors may impact the inflammatory responses (Doherty and Blatteis 1980;Fournier et al 2015;Ricciuti and Fewell 1992). Elucidating the effects of LPS on body surface temperature and cytokine responses is the first step in quantifying the interaction of LPS-mediated cytokine and thermal responses.…”
Section: Introductionmentioning
confidence: 99%
“…In neonatal rats, LPS injection tended to reduce f R and the ability to autoresuscitate from an anoxic challenge (Olsson et al, 2003). Conversely, previous observations in newborn rats (McDonald et al, 2016a) and piglets (McDeigan et al, 2003) showed that LPS injection did not alter respiratory variables during normoxia. In neonatal mice, LPS injection increased HR and altered cardiac performance (Mukherjee et al, 2010), while, in adult sheep, LPS injection reduced MAP, HR, and cardiac index after 60 min (Ferrara et al, 2019).…”
Section: Our Neonatal Ovine Model Of Lps-induced Systemic Inflammationmentioning
confidence: 80%
“…В этой связи в литературе подчёркивается необходимость дородового патронажа беременной с разъяснительными беседами о факторах риска по развитию смерти младенцев, важность всестороннего и полного наблюдения за новорожденным ребенком в родильном доме и в течение первого года жизни [2,25]. Следует отметить, что повышение качества и доступности медицинской помощи в сфере охраны материнства и детства является одним из важных элементов современной стратегии развития российского здравоохранения [26].…”
unclassified